EVALUASI KINERJA KONSELOR DALAM PROSES KONSELING DAN RISET KONSELING DI SEKOLAH - Ardimen Ardimen (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2017)
The purpose of this study was to describe the performance of counselors in the counseling process and the research process in high school. This study is an evaluation study to collect and analyze data systematically with regard to the performance of counselors in the counseling process and performance of counselors in research and the constraints that it faces. The results of this study indicate that the performance of counselors in the counseling process in general has been quite good, but in some aspects are still many weaknesses and shortcomings, among them: the data on identification of potential and problems of students is not complete, the purpose of counseling is not defined precisely in choosing / determining counseling intervention is still dominated by the problem of students, guidance and counseling services group and content mastery rarely implemented. Performance counselor in the research process is still tergolog very low because most of the counselors never carry PTK-BK, a small portion counselor believes that research counseling is less important and not important, most counselors rarely identify research questions, rarely formulate the design/ research proposal and a fraction counselor never established a design/ research proposal. The main obstacle counselor in research is lacking writing exercise science, lack of understanding of research methodology, less reading, there are no available references that are relevant, not master the technique of writing scientific, less able to formulate research problems, lack of awareness of the importance of research, lack of financial support, and a fraction counselor unskilled using a computer.